Bridging the Gulfs between Occidentalism and Orientalism - Ghulam Shabbir; Ussama Ahmed (Hazara Islamicus, 2021)
Islam believes in the essential unity of mankind, invites people of the Book on the platform of monotheism to strike an ethical world order that ensures justice, peace, progress, and prosperity for mankind. But when forces of history assumed an inimical attitude towards this end, keeping this invitation intact, Islam unilaterally took the plunge. Later Islam and the world of Christianity remained locked in the realm of political hegemony for centuries well until our times. The crusades and after Renaissance western aggressions against Muslim Asia and Africa and other historical biases rent asunder a wide artificial gulf between Islam and West. Recent tectonic shifts in the crisis-stricken world politics demand elimination of historical biases between Islam and the Judaic Christian West. This is exploratory research to find unalloyed truth from an ore of prejudiced history that leads to bridging the gulfs between Occidentalism and Orientalism.